Provoked Aggression: An Interplay between Self-control Training, Mindfulness Induction, and Provocation Sensitivity. Issue 5 (27th May 2020) - Yusainy, Cleoputri; Lawrence, Claire
ABSTRACT: Training in self-control and mindfulness have recently received empirical supports in the aggression literatures, but little is known about the efficacy of these interventions for those with greater sensitivity to aggression-provoking situation. On theoretical grounds, both interventions may operate in tandem at different points of a provoked aggression episode. Undergraduate participants ( N = 99; mean age 20.02, SD = 2.66; 51.5% female) were randomly assigned either to perform a 2-week self-control training of correcting posture or not, then they were orthogonally assigned either to experience a 10-min mindful walking exercise or relaxation control. Following these interventions, participants were provoked and given the opportunity for a retaliatory act of delivering an aversive noise blast. We found that less provoked aggression was associated with lower provocation sensitivity and participation in the self-control training, but was not associated with mindfulness induction by itself or via its interaction with other predictors. These findings indicated that interventions on aggressive behavior should not be examined alone; other factors such as for whom (i.e., individual differences), how (i.e., the interaction with another intervention), and when (i.e., aggression-provoking situations) should be taken into consideration for assessing the interventions.